The assessment of knowledge, attitude and practice towards tuberculosis infection control among health professionals in Nekemte referral hospital, Nekemte, Oromia, West Ethiopia: cross sectional facility based study - Golja, Eba Abdisa (International Journal of Infection Control, 2020)
Infection control remains a key challenge for Tuberculosis control program with an increased risk of Tuberculosis transmission among health care workers. Poor knowledge, poor practice and poor attitude among health care workers and inadequate infection control practices may lead to the increased risk of nosocomial Tuberculosis transmission. People living in the same household, or who otherwise are in frequent contact with an infected patient have the greatest risk of being exposed to the bacilli. This study was aimed to assess knowledge, attitude and practice of health professionals towards tuberculosis infection control in Nekemte referral hospital, Nekemte, west Ethiopia, 2018. Institutional based cross sectional study design was conducted from December 2017 to January 2018 among 223 health professionals in Nekemte referral hospital. Data was collected by using self-administered structured questionnaires which has subdivided components, and finally the analysis was done by double entry of SPSS version 21. Two hundred study participants responded to our current study with response rate of 200(89.6%). In this study, majority of respondents, 54% were females and 55% of them are first degree holders. From 200 participants, 14 (7%) had poor knowledge. Majority, 157(78.5%) of health care workers, had positive attitudes towards Tuberculosis infection control. Sixty (30%) of participants had poor practice. This study found that significantly high proportion of health workers had good knowledge and practice towards tuberculosis infection control. More than half of health workers wrongly believed that surgical mask can protect health workers from inhaling mycobacterium containing aerosols.